Webinar Penulisan Ilmiah sebagai Upaya dalam Meningkatkan Pemahaman Masyarakat terhadap Kemampuan Menulis - Huda, Ali Anhar Syi’bul; Alamsyah, Adam; Ridani, Muhammad Noor; Nurdiyanto, Nurdiyanto; Saputra, Wendi; Nurhuda, Abid (Jurnal Nusantara Mengabdi, 2024)
Purpose: The purpose of this study was to describe scientific writing webinar activities in an effort to increase public understanding of writing skills. Methodology/approach: The method used is an online field study via Zoom on September 9, 2023, with a participatory model in which scientific writing webinar activities include three important stages: planning, implementation, and evaluation. Results/findings: The results showed that the scientific writing webinar activities included a planning stage that had implications for making flyers that had to be disseminated en masse, followed by the webinar implementation stage, which consisted of opening, core activities, questions and answers, and closing, and finally the evaluation stage, which was in the form of feedback from participants to determine the level of understanding of the material and satisfaction with the webinar activities. Limitations: The limitation of this research is that only 64 people participated in the full writing webinar, and it is hoped that further research can study more participants than that, so that it is clear, detailed, and reinforces what has been produced. Contribution: This resulted in the acquisition of a percentage of material understanding level of 71.7% and the level of satisfaction of participants with the organization of the webinar was very satisfied and satisfied by 81.1%.